Faculty Development Autoethnographies: Engaging in Peer Coaching, Learning Communities, and Mentoring - Kathryn McAtee; Catherine A. Hansman (Adult Education Research Conference, 2013)
The primary purpose of this research is to explore examples of peer coaching, learning communities and mentoring as faculty development.